Contributions of the Semiotics of Culture for an effective diplomacy: Approach to the speeches of Vladimir Putin - FIOR, Asja; LUKIN, Oleg; MARTÍN BLANCO, Miguel Ángel (Journal of the Spanish Institute for Strategic Studies, 2023)
Following the approaches of the Semiotics of Culture, this article deals with the conflict accentuated between Russia and the West after the invasion of Ukraine. Specifically, three interventions by President Vladimir Putin during the year 2021 are analyzed in order to describe how the universe of meaning in which Russia is intended to be placed in the world and against its adversaries is configured. In this regard, the analysis focuses on the main isotopies of his discourse, on his narrative structure and on enunciative strategies. On this basis, the main oppositions that are established between Russian and Western culture and the reasons that make a friendly and constructive dialogue impossible at the present time are highlighted. It ends by proposing a look towards the future and arguing how a more effective diplomatic relationship between Russia and Europe could be promoted.